2014
DOI: 10.1242/jeb.099226
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific scaling of arterial blood pressure in the Burmese python

Abstract: Interspecific allometric analyses indicate that mean arterial blood pressure (MAP) increases with body mass of snakes and mammals. In snakes, MAP increases in proportion to the increased distance between the heart and the head, when the heart-head vertical distance is expressed as ρgh (where ρ is the density of blood, g is acceleration due to gravity and h is the vertical distance above the heart), and the rise in MAP is associated with a larger heart to normalize wall stress in the ventricular wall. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A negative relationship between heart rate and body mass had been previously reported in reptiles, and more specifically snakes (SEYMOUR 1987, LILLYWHITE et al 1999, ENOK et al 2014). Seymour's results are restricted to Australian snakes and were obtained from a small sample size (only 13 individuals in nine different species).…”
Section: Short Communicationmentioning
confidence: 60%
See 4 more Smart Citations
“…A negative relationship between heart rate and body mass had been previously reported in reptiles, and more specifically snakes (SEYMOUR 1987, LILLYWHITE et al 1999, ENOK et al 2014). Seymour's results are restricted to Australian snakes and were obtained from a small sample size (only 13 individuals in nine different species).…”
Section: Short Communicationmentioning
confidence: 60%
“…Even though most modern studies have used another method to measure heart rate, which includes a surgically inserted catheter filled with heparinized saline connected to a pressure transducer (WANG et al 2001, ENOK et al 2014, we have found that our method produces similar results (see discussions below for more details). Furthermore, digital palpation is easier to perform, cheaper, and safer for the subjects.…”
Section: Short Communicationmentioning
confidence: 62%
See 3 more Smart Citations